FORMULATION AND EVALUATION OF MOUTH DISSOLVING TABLET OF AMLODIPINE BESYLATE - BADWAR, MEGHAWATI R.; BORSE, SANDHYA L.; JUNAGADE, MANISH S.; JADHAV, ANIL G. (International Journal of Applied Pharmaceutics, 2019)
Objective: The main objective of this research work was to formulate and evaluate the mouth dissolving tablet of amlodipine besylate for the treatment of hypertension and coronary artery disease. Methods: In this study, mouth dissolving tablet were prepared by direct compression method by using croscarmellose sodium and sodium starch glycolate as superdisintegrants. The designed tablets were subjected to various assessment parameters like friability test, hardness test, disintegration test, wetting time, in vitro drug release and drug content. Results: All the prepared formulations were subjected to various assessment parameters, and the findings obtain within the prescribed limit. The calibration curve of pure drug using various solvents like phosphate buffer pH 6.8, methanol was plotted. F1-F9 containing croscarmellose sodium and sodium starch glycolate in various concentration demonstrate the minimum disintegration time. Among all these formulations F9 shows disintegration time up to 22±1.12 seconds due to the high concentration of superdisintegrants. In vitro drug release was tested in phosphate buffer pH 6.8 at a time interval of 0, 1, 2, 3, 4, 5 min. The F9 shows drug release 100.22±1.08%. Accelerated stability study of optimized formulation (F9) up to 2 mo showed there was no change in disintegration time and percentage drug release. Conclusion: The results obtained in the research work clearly showed a promising potential of mouth dissolving tablets containing a specific ratio of croscarmellose sodium and sodium starch glycolate as superdisintegrants for the effective treatment of hypertension and coronary artery disease.